Neutrophil Extracellular Traps: Potential Prothrombotic State Markers and Therapeutic Targets for Atrial Fibrillation - Liu, Xing; Li, Xinjian; Xiong, Shenglin; Zhang, Haipeng; Suo, Rong; Zhang, Xu; Liu, Daiqi; Fu, Huaying; Liu, Tong; Li, Guangping (Thrombosis and Haemostasis, 2023)
Background Recently, the mechanism of thrombogenesis has taken a new direction with the involvement of neutrophil extracellular traps (NETs). However, little is known about the relationship between NETs and thrombogenesis in atrial fibrillation (AF).Objective Our study aimed to evaluate NETs in AF patients and their potential association with thrombogenesis. In addition, we studied the effect of NETs on thrombogenesis in rat models.Methods A total of 125 AF patients and 172 controls were studied. Spontaneous echo contrast (SEC) was examined using transesophageal echocardiography to assess the prothrombotic state. We used rapid atrial pacing (RAP) rat models to study NETs' formation and their effects on thrombogenesis. The levels of NETs were analyzed by flow cytometry. To deeply understand the regulatory mechanism of NET formation, the transcriptional characteristics of the left atrial appendage (LAA) tissue from RAP rats were analyzed.Results We found that NETs were increased significantly in AF patients and positively correlated with SEC grades. And inserting the NET level could significantly enhance the predictivity of CHA2DS2-VASc scores for the AF prothrombotic state. In the RAP models, we observed that NET levels increased significantly in the LAA and promoted thrombosis. Meanwhile, we found that these changes could be suppressed by the NET formation inhibitor. Transcriptomic analysis of the LAA tissue from RAP rats suggested that RAP might stimulate the NET formation by promoting the expression of inflammatory cytokine and adhesion genes.Conclusion NETs may constitute useful thrombogenesis risk markers in AF patients and provide a potential therapeutic strategy for AF management.
Keywords: neutrophil extracellular traps; atrial fibrillation; thrombogenesis; spontaneous echo contrast; protein arginine deiminase 4; transcriptomic analysis